Basal cell carcinoma arising over lesion of discoid lupus erythematosus: a rare occurrence. (February 2020) - Pradhan, P; Samal, S; Sable, M
Although the association of discoid lupus erythematosus (DLE) with squamous cell carcinoma has been described in the literature, coexistence with a basal cell carcinoma is very rare. The indolent and non-pruritic nature of the lesion cause it often to be diagnosed at the late stage of the disease. Long-standing photosensitivity and chronic inflammation later lead to scarring and hypopigmentation, which are considered as the risk factors for the malignant changes over DLE. Incisional biopsy is often performed from the erythematosus lesion which does not respond to medical treatment. Here we have reported a rare case of basal cell carcinoma of the skin developing in the background of long-standing DLE, which was successfully managed with cold knife local excision.